Effects of order of acquisition : a brief study of the differences between late passive bilinguals and early balanced bilinguals - Chua, Andy Jun Hao (2016)
Age of acquisition (or order of acquisition) effects is a phenomenon that enables faster recognition and production of items encountered earlier as compared to those that are experienced later. In this study, the researcher attempted to study the combined effects of bilingualism and age of acquisition. Participants were recruited such that they fall into 2 categories: Late Passive and Early Balanced. The participants were trained in 30 Spanish names along with their corresponding object images. To induce age of acquisition effects, the participants were presented half of the items as “early” words, which were shown in the first training session. The “late” words were presented from the second training session, mixed with the “early’ words. The participants were exposed to all words for the same amount of times at the start of each test session. Test results showed that Early Balanced bilinguals were able to produce the learnt words faster when presented with the corresponding stimuli, as compared to the Late Passive Bilinguals. However, based on the analyzed data, there were no significant effect of the age of acquisition in learning a new language found between the two groups.